1962
DOI: 10.1111/j.1476-5381.1962.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Action of Tyramine and Its Interrelationship With the Effects of Other Sympathomimetic Amines

Abstract: Choline 2,6-xylyl ether potentiated the sympathomimetic effects of tyramine and adrenaline in anaesthetized and spinal cats; the effects of noradrenaline were not significantly affected. The pressor activity of tyramine was also potentiated by the drug in reserpine-treated spinal cats and in pithed rats. The acute intravenous injection of reserpine in pithed rats potentiated pressor responses to tyramine, but depressed those to adrenaline and noradrenaline. During the intravenous infusion of noradrenaline in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1963
1963
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…(Burn & Rand, 1958), the response to a single dose of noradrenaline was decreased during the high rates of infusion (5.5 [tg/min and above). Nasmyth (1962) has suggested that the action of tyramine may be modified by variations in the concentration of noradrenaline in the extracellular fluid, while Muscholl (1960) found that in the rat treated with reserpine noradrenaline increased the pressor responses to tyramine without replenishing the noradrenaline in the tissue stores. The present results show that as the rates of infusion of noradrenaline or of adrenaline were increased so the pressor response to tyramine was further increased but that to noradrenaline was further decreased.…”
Section: Effectsmentioning
confidence: 99%
“…(Burn & Rand, 1958), the response to a single dose of noradrenaline was decreased during the high rates of infusion (5.5 [tg/min and above). Nasmyth (1962) has suggested that the action of tyramine may be modified by variations in the concentration of noradrenaline in the extracellular fluid, while Muscholl (1960) found that in the rat treated with reserpine noradrenaline increased the pressor responses to tyramine without replenishing the noradrenaline in the tissue stores. The present results show that as the rates of infusion of noradrenaline or of adrenaline were increased so the pressor response to tyramine was further increased but that to noradrenaline was further decreased.…”
Section: Effectsmentioning
confidence: 99%
“…Another experiment that can be interpreted in the same way is that of Lindmar (125) who found that the sympathomimetic action of tyramine (but not that of nicotine) on the auricles of guinea pigs pretreated with reserpine could be restored by the presence of small concentrations of NE in the bath fluid. N asmyth (141) in an investigation of the action of tyramine and its interrelationship with the effects of other sympathomimetic amines, concludes that his results are inconsistent with the view that the sympathomimetic effects of tyramine are produced entirely by the release of catechol amines. So while more quantita tive experiments are needed, the above results are in harmony with the concept that the indirect-acting sympathomimetic amines require for their action small amounts of catechol amines as catalysts.…”
Section: Non-catechol Amines and Their Mechanism Of Actionmentioning
confidence: 84%
“…Although pretreatment with reserpine abolishes the response to indirectly acting sympathomimetic amines when these are administered some 12 to 24 h later, the responses are enhanced when the alnines are given immediately after reserpine (SCHMITT and SCHMITT, 1960;NASMYTH, 1962;SCHMITT et al, 1962). The pressor response ofthe cat to iso-monomethylnicotinium bromide (a weak nicotinic stimulant) is markedly enhanced when it is given soon after a low dose of reserpine which itself has no action (EULER and PERSSON, 1970).…”
Section: Sympathomimetic Responses To Reserpinementioning
confidence: 96%